OPTIMALISASI PEMANFAATAN VIDEO SEBAGAI ALAT PROMOSI UNTUK MENINGKATKAN POPULARITAS DESA WISATA BAKAS, KLUNGKUNG - Sari, Retno Juwita; Ida Ayu Etsa Pracintya; I Wayan Putra Aditya (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
The digitalization 5.0 nowdays needs to be studied in order to adapt with the tourism developments over time, including in the promotion sector. One of the developing tourism village is Bakas. Bakas Tourism Village has taken advantage of existing digitalization opportunities by promoting its potential attractions through Instagram social media. Bakas Tourism Village which located in Klungkung district, is a tourist village that has the potential for natural, culinary and spiritual tourist attractions. It is important to maximize the use of social media, to promote the various attractions of Bakas Tourism Village. The aim of this program was to help the stake holders in Bakas Tourism Village to carry out promotions on social media, by editing videos and photos using the features offered to edit in various social media. The results of this training were; (1) Developing business social media account, (2) Uploading photos of that have been edited using various editing features, (3) Uploading videos by adding interesting filters, captions and songs. In conclusion, these three outputs can make the products they offer more attractive before uploading them to social media accounts.